2014
DOI: 10.14748/ssm.v46i1.642
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of liver hydatid disease

Abstract: E. granulosis is the species that prevails in most countries around the world and especially in the Mediterranean region. It is one of the most severe infestations in humans. The biological diagnosis is based on serological tests. Eosinophilia is considered variable because it does occur in cases of a hydatid cyst disease but its absence does not exclude the possibility of a hydatid cyst existence. Imaging diagnostics are important for the classification of the hydatid cysts. Ultrasound is a noninvasive, widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This is supported by the present fi ndings, as only 39 (72.2%) of the 54 patients had positive ELISA results. Because the results of immunological diagnostic methods vary, they are insuffi cient as a single test for defi nitive diagnosis (21) . In the present study, a defi nitive diagnosis of hydatid cyst was confi rmed by direct parasitological examination and identifi cation of protoscolices and refractile hooks.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the present fi ndings, as only 39 (72.2%) of the 54 patients had positive ELISA results. Because the results of immunological diagnostic methods vary, they are insuffi cient as a single test for defi nitive diagnosis (21) . In the present study, a defi nitive diagnosis of hydatid cyst was confi rmed by direct parasitological examination and identifi cation of protoscolices and refractile hooks.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with our work, as only 39 cases (72.2%) out of the 54 cases included in the study had positive ELISA readings. The immunological diagnostic methods show variable results, therefore proving insufficient as a single test for the exact diagnosis [21]. In the present study, a definite diagnosis of hydatid cyst was confirmed by direct parasitological examination and identification of protoscolices and refractile hooks.…”
Section: Discussionmentioning
confidence: 44%